Neonatal dengue with enterococcus sepsis - Chopra, Sanya; Kapoor, Saurabh; Jain, Suksham; Chawla, Deepak (Indian Journal of Case Reports, 2018)
Dengue infection is possible in all the three trimesters of pregnancy and is associated with various maternal and neonatal complications. The occurrence of subclinical infections may lend further confusion to the situation. Here, we report a case of neonatal dengue diagnosed with dengue NS1 antigen positive and IgM positive followed by secondary sepsis with Enterococcus faecium. Case studies like these may contribute to increased awareness of the suspicion of the associated life-threatening infections that can occur with neonatal dengue, their manifestations, and the management, thus improving their outcome.